The Intra-country Distributional Impact of Policies to Fight Climate Change : A Survey - Boccanfuso, Dorothee; Estache, Antonio; Savard, Luc (2012)
In this paper, we present a survey of distributional impact analysis of environmental policies with emphasis on taxes envisaged or implemented to reduce greenhouse gas emissions (GHG). These policies usually aim at reducing GHG directly or indirectly. However, they can produce important changes in factor allocation, relative prices in specific countries as well as on world markets when adopted by a large number of countries. Changes in welfare can be important for vulnerable groups of population in developing countries. This survey reviews the evidence on the incidence of these policies. In the process, it shows that the computable general equilibrium (CGE) microsimulation approach has not been fully exploited in the context.